Mutagenic analysis of the coronavirus intergenic consensus sequence. - Joo, M (1992)
Previously, a system in which an intergenic region from mouse hepatitis virus (MHV) inserted into an MHV defective interfering (DI) RNA led to transcription of a subgenomic DI RNA in helper virus-infected cells was established. In the present study, a DI cDNA containing one UCUAAAC consensus sequence in the middle of the 0.3-kb-long intergenic region located between genes 6 and 7 was constructed. From this DI cDNA clone, 21 mutant DI RNAs were constructed so that each of the seven consensus sequence nucleotides was changed individually to the three alternative bases. These mutants were used to define how changes in the integrity of MHV transcription consensus sequence UCUAAAC affected mRNA transcription. Except for two mutants with the sequences UGUAAAC and UCGAAAC, all of the mutants supported efficient subgenomic DI RNA transcription. This indicated that MHV transcription regulation was sufficiently flexible to recognize altered consensus sequences. Next, these and other mutants were used to examine the leader-body fusion site on the subgenomic DI RNAs. Sequence analysis demonstrated that all subgenomic DI RNAs analyzed contained two pentanucleotide sequences; the first sequence seemed to be contributed by the leader, and the leader-body fusion most likely took place at either the first or the second nucleotide of the second sequence. This observation was not consistent with the proposed coronavirus transcription model (S. C. Baker and M. M. C. Lai, EMBO J. 9:4173-4179, 1990) which states that nucleotide mismatch can be corrected by RNA polymerase proofreading activity.